Prevention of in-stent restenosis via reduction of thrombo-inflammatory reactions with recombinant P-selectin glycoprotein ligand-1 - Tanguay, Jean-François; Geoffroy, Pascale; Sirois, Martin G.; Libersan, Danielle; Kumar, Anjali; Schaub, Robert G.; Merhi, Yahye (Thrombosis and Haemostasis, 2004)
The binding of leukocyte P-selectin glycoprotein ligand-1 (PSGL-1) to platelet P-selectin is central to post-angioplasty restenosis. Although intracoronary stents limit the mechanical component of restenosis, they cause marked thrombo-inflammation and neointimal proliferation leading to greater late luminal loss. We sought to demonstrate that P-selectin antagonism, using recombinant PSGL-1 (rPSGL-Ig), is effective in reducing platelet-leukocyte reactions and in-stent restenosis in doubleinjured porcine coronary arteries. Two weeks after initial injury by angioplasty to the coronary arteries, stents were implanted at the injury-induced lesion site, 15 min after an IV bolus administration of a vehicle or rPSGL-Ig (1 mg/kg). Four weeks later, adhesion of 51Cr-platelets and 111In-neutrophils and histomorphometric analyses were performed. In-stent residual lumen was almost 3 fold larger in rPSGL-Ig-treated arteries (3.1 ± 0.4 mm2) as compared to control (1.1 ± 0.2 mm2), which correspond to 64% vascular stenosis in control with no change in rPSGL-Ig animals. For a similar injury score, in-stent neointima was significantly reduced by 30 to 40% in the rPSGL-Ig group and quantitative coronary angiography showed a significant 35% reduction in late lumen loss. These effects of rPSGL-Ig were associated with a respective 70% and 53% reduction in platelet and neutrophil adhesion. In conclusion, pretreatment with rPSGL-Ig reduces thrombo-inflammatory responses, neointimal proliferation, and in-stent restenosis. P-selectin antagonism offers a promising therapy to improve clinical outcomes of coronary stenting.
Keywords: Restenosis; stents; leukocytes; platelets; P-selectin; PSGL-1